Influence of fiber type and matrix composition on adhesive strength in fiber reinforced concrete - Yu. V. Pukharenko; D. A. Panteleev; M. I. Zhavoronkov (Вестник СибАДИ)
Introduction. The purpose of the article is to determine the influence of the steel fiber profile and the composition of the matrix on their adhesion in dispersed reinforced concrete.Materials and methods. Studies have been carried out using the test methods set out in national standards. To determine the characteristics of the adhesion strength of fibers with a matrix, an original technique developed at SPbGASU was used.Results. The degree of influence of the geometric shape of steel fibers – anchor and wave profile on the adhesion strength characteristic is determined. The adhesion strength of steel fiber with cement and concrete matrix was assessed (Cement: Sand = 1:1, Cement: Sand = 1:2 and Cement: Sand = 1:3). The influence of the volume fraction of the cement paste on the characteristic of the adhesion strength of the steel fiber with the matrix has been experimentally proven.Conclusions. The experimental data obtained confirm the effectiveness of dispersed reinforcement through the use of anchor fibers in combination with a rationally selected composition of the concrete matrix.